Whole-Brain Radiotherapy Combined With Anlotinib for Multiple Brain Metastases From Non-small Cell Lung Cancer Without Targetable Driver Mutation: A Single-Arm, Phase II Study. (February 2022) - Liu, Jianjiang; Xu, Jun; Ye, Wanli; Zhong, Wangyan; Zhang, Xiaoyu; Mao, Jiwei; Wu, Dongping
Background: Existing evidence demonstrates that radiotherapy and antiangiogenic drugs have synergistic antitumour effects and may be a promising treatment option for patients with solid tumour. Thus, we performed a phase II trial to evaluate the efficacy and safety of whole-brain radiotherapy (WBRT) combined with anlotinib for multiple brain metastases (BMs) from non-small cell lung cancer (NSCLC) without targetable driver mutations. Methods: Patients with multiple BMs (⩾3) from NSCLC without targetable driver mutations who failed to respond to at least first-line chemotherapy were enrolled. Eligible patients received WBRT (30 Gy/10 f, 5 f/week) and anlotinib (12 mg/day, day 1-14 of 21 days per cycle, 2 cycles) until disease progression or treatment intolerance. The primary endpoint was intracranial objective response rate (iORR) and secondary endpoints included intracranial progression-free survival (iPFS), disease control rate (DCR), overall survival (OS), and safety. Results: Between April 2019 and March 2021, 21 patients were enrolled in the trial, of which 12 were aged ⩾60 years (57.1%), 13 were men (61.9%), 7 had an Eastern Cooperative Oncology Group Performance Status score of 0 to 1 (81.0%), 18 had adenocarcinoma (85.7%), and 11 had ⩾6 BMs (52.4%). Of the 21 evaluable patients, the iORR was 66.7% (1 complete response + 13 partial response [PR]), and 28.6% (7PR) had extracerebral lesions. The DCRs for intracerebral and extracerebral lesions were 90.5% and 81.0%, respectively. The iPFS and OS were 10.3 months (95% confidence interval [CI]: 0-24.8 months) and 13.4 months (95% CI: 0-27.9 months), respectively. The most frequently observed toxicities were loss of appetite (61.9%), hypertension (52.4%), fatigue (47.6%), diarrhoea (28.6%), vomiting (19.0%), dizziness (42.9%), and headache (33.3%). None of the patients developed grade 4 or higher grade adverse reactions. Conclusions: Anlotinib combined with WBRT is effective and well tolerated in patients with multiple BMs (⩾3) from NSCLC without targetable driver mutations. Therefore, further validation studies are required. Clinical trial registration number: ChiCTR 1900027769